Constructing liquid marble as particle-assembled microdroplet for multiplex sensing and reaction modulation/monitoring - Lee, Hiang Kwee (2017)
Liquid marbles are particle-assembled microdroplet platforms that have garnered paramount importance as both microsensor and microreactor owing to their excellent robustness, highly customizable properties as well as need of minute sample/reaction volumes. However, three main challenges relevant to the field have been identified; (1) limitation of molecular sensing to a single fluid phase, (2) invasive and ex-situ reaction monitoring techniques and (3) lack of heating mechanism and active mass transportation system for reaction control. The objectives of my thesis therefore aim to address these limitations, empowering liquid marbles as efficient and multifunctional micro-sensors/reactors applicable in broad scientific/technological fields such as nanotechnology, green processes, and synthetic chemistry. In chapter 2, we demonstrate the fabrication of plasmonic liquid marble prepared using Ag particles as a multiplex SERS sensor capable of identifying and quantifying analytes present across an immiscible liquid-liquid interface. Such plasmonic liquid marble is further exploited as a microreactor-sensor hybrid in chapter 3 for the rapid and on-site read-out of reaction events within the microreactor at the molecular-level. Chapter 4 and 5 mainly focus on the enhancing and tuning of reaction kinetics using liquid marble-based microreactors. For chapter 4, we apply graphene liquid marble as photothermal-active miniature reactor to remotely control its temperature for direct kinetic modulation on the encapsulated reaction. In chapter 5, we demonstrate the spinning of a magnetically-active liquid marble to induce an active mass transportation system within the enclosed 3D microdroplet. Such spinning phenomenon imparts a spiral acceleration of enclosed molecules towards the exterior encapsulating shell for improved catalytic performance and controllable reaction dynamics. Lastly, I conclude my thesis with a summary of my four-year research works and provide an outlook for continuous and significant progress in this emerging field.